An index for corporate governance quality assessment in Brazil - Correia, Laise Ferraz; Amaral, Hudson Fernandes; Louvet, Pascal (Revista Contabilidade & Finanças, 2011)
The purpose of this paper is to build an index to measure the quality of governance of Brazilian companies. We also sought to validate this index by confronting it with other indicators that reflect the confidence of investors in companies' good management of their capital. This index encompasses a set of mechanisms implemented in firms to reduce agency problems, concerning the dimensions: board of directors' composition, ownership structure, manager's compensation, protection of minority shareholders, and transparency. It was then validated in a sample of companies listed on São Paulo Stock Exchange (Bovespa) between 1997 and 2006. In fact, the index was confronted with indicators of financial investors' trust in a company regarding good governance of their resources, such as financial performance. The quality of governance index was developed by means of the principal components multivariate technique. Actually, the index was constructed as a weighted average of all components generated in this procedure, where the weights are given by their respective variances. The analysis of our index exhibited an effective accrue in the governance levels of the analyzed Brazilian companies. In terms of external validation, we find a positive and significant relationship between Tobin's Q and the governance index. Better, we also document an inverse relationship between the governance index and the risk-adjusted stock return, suggesting that investors require a higher rate of return from firms that present worse governance levels. All of these relationships evidence that financial investors' trust in a company strongly relates to the governance quality expressed by the index. Therefore, the empirical analysis largely validates the proposed governance index. We conclude from the empirical evidence reported in this paper that good governance is of value to the market.